Perbedaan Perilaku Gosip pada Mahasiswa Universitas Negeri Padang Ditinjau dari Jenis Kelamin, Kelompok Usia dan Kelompok Studi - Rizal, Adi Achirul; Utami, Rahayu Hardianti (Lembaga Yasin AlSys, 2024)
Nowadays social phenomena are influenced by the exchange of information in it. The exchange of information where people gather and talk about building an interaction with others is a collective culture called gossiping behavior (Sulistyowati, 2016). This study aims to look at differences in gossip behavior between men and women, late adolescents and early adults, as well as social and scientific study groups in State University students. The sample collection technique used proportional random sampling technique using the Gossip Functions Questionare (GFQ) scale. The results of the measuring instrument reliability test were 0.865 and data analysis using two-way anova and mann witney. The results showed that there were no differences in gossiping behavior based on gender indicated by a p value = 0.90 (p> 0.05). There is no difference in gossiping behavior based on age group with a p value = 0.602 (P> 0.05) and there is no difference in gossiping behavior based on study group because the p value = 0.321 (p> 0.05).